Medical students’ personal experiences, religion, and spirituality explain their (dis)comfort with a patient’s religious needs - Cindy Schmidt (Canadian Medical Education Journal, 2020)
Background: Physicians often avoid discussing patients’ religious and spiritual concerns, even though most patients (i.e., 50-94%) want integrated care.  To address this gap, medical students interviewed a Standardized Patient (SP) who was upset because the daughter did not confront her fiancée about converting to Orthodox Judaism.  Students reflected on how their own religion and spirituality affected engaging with their patient.